Hidradenocarcinoma in a young Caucasian male, arising from a metatarsophalangeal joint and presenting with inguinal lymphadenopathy. Issue 2 (2018) - Kuah, Chii Yang; Gan, Jaslyn Ju Lia; Nicholson, Steve
No abstract available